2013
DOI: 10.1371/journal.pone.0057287
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Mouse Uterus at Pre-Implantation Stage under VEGF Repression

Abstract: Uterus development during pre-implantation stage affects implantation process and embryo growth. Aberrant uterus development is associated with many human reproductive diseases. Among the factors regulating uterus development, vascular remodeling promoters are critical for uterus function and fertility. Vascular endothelial growth factor (VEGF), as one of the major members, has been found to be important in endothelial cell growth and blood vessel development, as well as in non-endothelial cells. VEGF mediatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…Gain and loss of gene function are the basic techniques used for gene function studies and drug‐target screening. RNA‐Seq, which is based on the second‐generation sequencing technology can provided accurate and high throughput measurement of gene expression and are increasingly used in gene regulation studies. In this study, we analyzed the inhibitory effect of c‐Fos and GADD45β on T24 cells, through transfection and comparative transcriptomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Gain and loss of gene function are the basic techniques used for gene function studies and drug‐target screening. RNA‐Seq, which is based on the second‐generation sequencing technology can provided accurate and high throughput measurement of gene expression and are increasingly used in gene regulation studies. In this study, we analyzed the inhibitory effect of c‐Fos and GADD45β on T24 cells, through transfection and comparative transcriptomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports on the expression and function of KRT86 in the uterus; however, some information can be obtained from homologues. For example, KRT85, another member of the keratin family, is also expressed in the uterus [16]. Like KRT86, it also forms type II hair keratin and nails, and is a basic protein [17].…”
Section: Discussionmentioning
confidence: 99%
“…Like KRT86, it also forms type II hair keratin and nails, and is a basic protein [17]. In a vascular endothelial growth factor (VEGF) regulating implantation model, VEGF repression caused implantation failure, and Krt85 is dramatically up-regulated (1000 fold), indicating a role of keratin during implantation [16]. In alopecia areata (AA) lesional skin, Krt85 and Krt86 were significantly repressed [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that VEGF, by regulating vascular permeability, induces blood vessel leaking in ovaries exhibiting ovarian hyperstimulation syndrome (OHSS) (13). Notably, in a transgenic mouse model with engineered inducible repression of VEGF, mice were observed to become infertile upon VEGF repression (14 2,398 VEGF-regulated differentially expressed genes were identified in the mouse uterus, which indicated that VEGF exerts a regulatory role in gene expression in the uterus. The majority of studies regarding AMH focus on the early stage of follicle development.…”
Section: Introductionmentioning
confidence: 99%